Potential utilization of waste nitrogen fertilizer from a fertilizer industry using marine microalgae - Hareb Al-Jabri (17092903) (2021)
This study investigated the feasibility of microalgal biomass production using waste nitrogen fertilizers (WNFs) generated by the Qatar Fertiliser Company (QAFCO). From the plant, three types of WNFs (WNF1, WNF2, and WNF3) were collected; WNF1 and WNF2 had high solubility (e.g., 1000 g/L) whereas WNF3 had low solubility (65 g/L). For a lower dosage (i.e., 100 mg N/L) of these WNFs, >98% of nitrogen was soluble in water for WNF1 and WNF2; however, 52 mg N/L was soluble for WNF3. Nitrogen content in these wastes was 44, 43, and 39% for WNF1, WNF2, and WNF3, respectively. As these WNFs were used as the sole nitrogen source to grow Tetraselmis sp., Picochlorum sp., and Synechococcus sp., Tetraselmis sp. could utilize all the three WNFs more efficiently than other two strains. The biomass yield of Tetraselmis sp. in a 100,000 L raceway pond was 0.58 g/L and 0.67 g/L for mixed WNFs (all WNF in equal ratio) and urea, respectively. The metabolite profiles of Tetraselmis sp. biomass grown using mixed WNFs were very similar to the biomass obtained from urea-added culture – suggesting that WNFs produced Tetraselmis sp. biomass could be used as animal feed ingredients. Life cycle impact assessment (LCIA) was conducted for six potential scenarios, using the data from the outdoor cultivation. The production of Tetraselmis sp. biomass in QAFCO premises using its WNFs, flue gas, and waste heat could not only eliminate the consequences of landfilling WNFs but also would improve the energy, cost, and environmental burdens of microalgal biomass production. Other Information Published in: Science of The Total Environment License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.scitotenv.2020.142532